HUBUNGAN PENINGKATAN TEKANAN INTRAVESIKA URINARIA DENGAN PERDARAHAN INTRAPERITONEAL AKIBAT TRAUMA TUMPUL ABDOMEN - Soemarko, M. (Jurnal Kedokteran Brawijaya, 2004)
The diagnosis of intraperitoneal hemorrhage must bequickly with a high accuracy, before an acute exploratory laparotomy. This study was conducted to find out if intravesical pressure measurement should be as an alternative indicator of diagnostic peritoneal lavage in predicting intraperitoneal hemorrhage that indicating an acute exploratory laparotomy. Using an Explorative, Cross Sectional Design. Results of the exploratory laparotomy were used as  a standard of determining the accuracy of Diagnostic Peritoneal Lavage and intravesical pressure measurement in predicting theindication for the exploratory laparotomy. 18 of 24 patients has positive results of diagnostic peritoneal lavage, but an active intraperitoneal hemorrhage only found in 15 patients, witha positive predictive value 83,33 %, negative predictive value 100%. The results of intravesical pressure measurement in the same patients predicted 17 patients has positive results, with slight a higher positive predictive value (88,24 %), negative predictive value  100%. The conclusion is the measurement of intravesical pressure is an alternative procedure of Diagnostic Peritonel lavage for predicting intraperitoneal hemorrhage. Key words:Blunt Trauma Abdomen; Intravesical Pressure Measurement; Diagnostic Peritoneal Lavage; Exploratory Laparotomy; Intraperitoneal Hemorrhage.